Time-Dependent Relationships Between Human Brain and Body Temperature After Severe Traumatic Brain Injury - Childs, Charmaine; Liu, Kun; Vail, Andy; Pan, Jianxin (International Journal of Statistics in Medical Research, 2013)
There is uncertainty about the reliability of using body temperature readings as a ‘surrogate’ measure of brain temperature. Aim: To determine the temporal inter-relationship between body and brain temperature after severe traumatic brain injury (TBI). Setting and Patients: Large University teaching hospital in the North West of England. Patients admitted for emergency neurocritical care. All patients received dual-modality monitoring of brain tissue pressure and temperature via invasive intracerebral micro-sensors. Body temperature was measured using an indwelling thermistor inserted in to the rectum. Methods: Temperature was monitored continuously with values stored to a bedside data acquisition system at intervals of 10 minutes. Data were transferred to a spreadsheet at end of each individual’s monitoring period for further analysis under Matlab routines. The method of functional principal components was used to determine the time-dynamics of brain and body temperature relationships. Results: In the period after severe TBI, median body and brain temperature for all readings and in all patients was 37.6oC and 37.7oC respectively; a statistical (p <0.001) but not clinically significant difference. A strong regression relationship between brain and body temperature was demonstrated (functional coefficient of determination, R2= 0.7623, p< 0.0020). Conclusions: Body temperature is a good early predictor of brain temperature but only during the first two days after severe TBI. The results will be of value for future predictive modeling of brain temperature changes, particularly where brain tissue monitoring is not clinically justified or available. In particular, results demonstrate the uncertainty in using body temperature as a surrogate for brain temperature beyond the first two days after severe traumatic brain injury.